Fotografía y realidad: notas para una fenomenología del cine documental - Rubén Dittus (Doc On-Line: Revista Digital de Cinema Documentário, 2011)
This paper presents, from the Roland Barthes's semiotic, the regimen oftruth that make documentary cinema and photography elements of the same conceptualterritory. This is a phenomenological proposal that, by extension, defines documentarycinema as part of a cinematographic specificity that moves between two thresholds: thehighly codified cinematographic language and the referential identification.